Tat Twam Asi: Transformasi Individualistis Kearah Solidaritas Sosial - I Putu Agus Aryatnaya Giri; I Made Girinata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Humans as individual beings do not only mean the unity of body and soul, but will become a unique person with a personality style, including their abilities. Thus, humans as individuals are separate persons, different from other persons. Humans as individual beings are humans as individuals who have their own characteristics. In facing their natural environment, humans must live in companionship with other humans and this association gives them soul satisfaction. Tat Twam Asi as a moral teaching, always prioritizes love, devotion is willing to sacrifice unconditionally. Tat Twam Asi is a concept of the supreme teachings of Hinduism that teaches humans to always live in harmony together in the social sphere, helping each other, honing, loving, and nurturing. This is what is called an individualistic transformation towards harmonious social solidarity. Keywords: Tat Twam Asi, Individualistic, Social Solidarity